Pembuatan Briket Dari Batang Sawit Menggunakan Gliserol Produk Samping Biodiesel Sebagai Matrix - Aswie, Viqha; Helwani, Zuchra; Fatra, Warman (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Palm oil waste is one of the potential biomass to be converted into briquettes. The size of the particles, the composition of the matrix crude glycerol on palm oil charcoal and the pressing pressure has an effect on the quality of the briquettes produced. This study aims to determine the effect of particle size, composition of matrix crude glycerol on palm oil, and pressing pressure in briquettes produced from palm oil, and analyze the effect of these variables using the analysis of Respond Surface Methodology (RSM). The palm stem is first carried out by a carbonization process to form palm oil charcoal. Palm oil charcoal is separated by 60, 80, and 100 mesh sieve and mixed with crude glycerol with the composition of charcoal to crude glycerol 60:40, 70:30, and 80:20. The samples that have been mixed are then densified at 100, 110 and 120 kg / cm2. The design of the experiment trip was determined by Central Composite Design in Design Expert 7.0.0 software. The resulting briquette products were analyzed in the form of heat value analysis, compressive strength analysis, and proximate analysis. The results showed that the highest calorific value was obtained at 28,089.6 kJ / kg in 80 mesh particle size, 53:47 charcoal matrix composition, and pressing pressure 110 bar. While the highest compressive strength value was 7,526 kg / cm2 at 10 mesh particle size, matrix composition of 80:20 charcoal, and pressing pressure 120 bar. Palm oil briquettes have met the standard heat value of briquettes (min. 21,000 kJ / kg) based on SNI.Keywords : briquettes, crude glycerol, matrix, palm prees